THE EFFECT OF PAYROLL CONTROL SYSTEMS AND PERFORMANCE BENEFITS ON EMPLOYEE PERFORMANCE AT BAPPELTIBANGDA CIANJUR DISTRICT - Gunawan, Asep; Saepudin, Didin; Aripin, Zaenal (KRIEZ ACADEMY : Journal of development and community service, 2024)
The purpose of this study was to determine the effect of the Payroll Control System and Performance Benefits on Employee Performance at Bappeltibangda Cianjur Regency. The research method used is descriptive research, which analyzes research results without drawing broader conclusions. This research involves independent variables, namely Payroll Control System (X1) and Performance Allowance (X2), as well as the dependent variable, namely Employee Performance (Y). Data collection techniques were carried out through field studies with questionnaires distributed to 84 respondents, and literature searches. Based on the results of the study, it can be seen that there is a significant relationship between the Payroll Control System, Performance Benefits, and Employee Performance at Bappeltibangda Cianjur Regency. The results of statistical calculations using SPSS show the value of F = 51.503, and the value of Sig. = 0,000. With the calculated F value above the F table (3.11) and the Sig value. <0.05, H0 is rejected, so Ha is accepted. This means that the Payroll Control System (X1) and Performance Allowance (X2) variables together have a significant effect on the Employee Performance variable (Y).